(untitled) (Applied Biological Research, 2023)
In the present study, the photosensitizing activity of phycocyanin and bacterio rhodopsin pigments derived from Halobacterium and a cyanobacterium, isolated from solar saltpan sediments of Cape Comorin coast of Tamil Nadu (India), was assessed. Halobacterial strains were grown on halophillic agar and Zobell marine agar; and pigmented bacteria identified on the basis of morpho biochemical characteristics. Cyanobacteria mats, gathered from the same environment, were grown on BG11 medium, and identified on the basis of morpho-biochemical characters as Oscillatoria sp., Spirulina sp. and Microcystis Phycocyanin pigment was extracted from these cyanobacteria while bacteriorhodopsin pigment was extracted from Halobacterium sp. The pigments were extracted by a centrifugation process, and characterised by HPLC and UV spectroscopy. In addition, the photosensitization capacity of pigments was evaluated using TiO2 thin film. The photosensitizing activity was assessed through band gap energy study using UV spectral analysis which was confirmed by FTIR and SEM analysis. Four probe tests were performed to measure the resistivity and conductivity of halobacterial and cyanobacterial pigment-coated TiO2 thin films.